Visible-Light-Driven Metal-Free and Photocatalyst-Free Intramolecular Cyclization of Chalcones to Access Phenanthrenes - Yi, Miaoyan; Zhang, Chen; Liao, Saihu; Sun, Bing (Synlett, 2024)
We report a visible-light-driven metal-free and photocatalyst-free protocol for the synthesis of phenanthrenes through the intramolecular cyclization of chalcones. The transformation proceeds through light irradiation and base- and oxygen-based promotion, and enables the generation of a series of phenanthrenes. The further functionalization of an as-synthesized phenanthrene to afford a fluorescent molecule was explored.
Keywords: photocatalysis; chalcones; phenanthrenes; intramolecular cyclization; fluorescence